EFFECT OF ADDING PENTOXIFYLLINE AND NITRIC OXIDE TO TRIS EXTENDER ON SOME POST-CRYOPRESERVED SEMEN ATTRIBUTES OF HOLSTEIN BULLS - & et al., Mohammed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to explore the effect of adding pentoxifylline (PTX) and nitric oxide (NO) to Tris extender on some post-cryopreserved semen attributes of Holstein bulls for different preservation periods (cooling at 5◦C, 48 hrs., 1, 2 and 3 months post cryopreservation, PC). Seven Holstein bulls of 2.5-3 years old were used in the current study during the period from 20th November, 2017 to 20th August, 2018. Pooled semen was equally divided into three groups within one experiment. PTX (0.192 g / 100 ml extender) and NO (0.018 g / 100 ml extender) were added to Tris extender and comparisons in response were made with the control group (Tris extender, C). The PTX group exhibited greater (P≤ 0.01) sperm's cell individual motility percentage as compared with the C group at cooling (5ºc) and 48 hr PC periods, while, PTX and NO groups were superior in these percentages at the remaining PC periods than C group. Excluding data of 2 months PC, greater (P≤ 0.01) live sperm percentage was observed in PTX and NO groups in comparison with the C group at all preservation periods. Lesser (P≤ 0.01) abnormal sperm percentage were noticed for PTX and NO groups as compared with the C group at all preservation time periods. The PTX and NO groups exhibited greater   (P≤ 0.01) acrosome and plasma membrane integrity percentages in comparison with the C group at all preservation time periods. In conclusion, adding PTX and NO to Tris extender enhanced some of  PC semen characteristics of Holstein bulls at different preservation periods.